Experience of Organizing Project Activities of Schoolchildren in the Field of “Information Technologies”. - S. V. Vishnyakov; V. I. Lazarev; Y. N. Vishnyakova (Открытое образование (Москва), 2024)
The article is devoted to analysis of the experience of organizing project work of schoolchildren in the field of information technologies on the basis of a higher educational institution.The peculiarities of the educational process organization, approaches to solving the problem of students’ motivation are considered. The principles of introducing relatively complex and science-intensive technologies into the projects of 10th grade students are discussed. Recommendations for organizing master classes and laboratory works with mastering the methods of image processing, steganography, machine learning are detailed. Emphasis is placed on the recycling of knowledge and skills acquired at school. Considerable attention is paid to visibility, comprehensibility of the results obtained, and the possibility of assessing the applicability of a particular method for solving the tasks of project activities. All works are carried out in such a way that pupils could start research with minimum effort for preparation and would be able to later transfer the learned tools to their individual projects. Much attention is paid to the methodology of project work, and special events are organized, such as pitch sessions of startups, designed to further motivate students, help them to organize their project work in a systematic way, and adjust the goals and objectives of their projects. Some results of the project work of schoolchildren in the field of information technologies during the 2023-2024 academic year on the basis of the National Research University “MPEI” are given.